Satellite based maritime surveillance to increase safety, security and efficiency of ship traffic - Lehner, Susanne; Schwarz, Egbert; Nyenhuis, Michael (2015)
With 90% of all goods being transported on sea routes an efficient, internationally competitive maritime industry is of high overall economic significance. The global exchange of goods is rising steadily causing an increase of ship traffic. New fuel efficient and safe routes are being discussed. In addition, tourism plays an increasingly important economic role at sea. To increase safety, security and efficiency of shipping and to protect the oceans, global data that provide reliable information about storms and sea state, sea ice cover, environmental pollution and ship locations are of paramount importance. This article demonstrates the use of the two German high resolution X-band radar satellites TerraSAR-X and TanDEM-X to develop maritime surveillance products, including ship detection and traffic monitoring or wind and sea-state information. The products are generated independently of weather conditions and in near-real-time and are delivered to operational users.